Social Values towards Time and Their Effect on Sustainable Development Performance. - Gleason, Nancy. (2017)
Abstract: This research examines whether sustainable forest management, a proxy for sustainable development performance, is influenced by social values towards time, known as temporal orientation. Temporal orientation is the way an individual views time, and future-directed temporal orientation relates to the anticipated causality of future events. This research tested the congruence between sustainable forest management and future-directed temporal orientation in three case studies, Guyana, Papua New Guinea and Suriname. Sustainable forest management performance was measured by applying seven specific criteria and indicators. Future directed temporal orientation was measured using five identified behavioral expressions: precautionary behavior, values toward intergenerational equity, access to quality education, corruption levels and the prevalence of secure property rights. Of the five identified social values reviewed here intergenerational equity, precautionary behavior, and property rights all demonstrated strong predictability of future-directed temporal orientation. However, education and corruption failed to provide definitive evidence of temporal orientation due to intervening variables. The main finding is that future-directed social values do positively correlate with strong sustainable forest management performance. Guyana's strong sustainable forest management correlated strongly with future directed temporal orientation, and Papua New Guineas relatively weak sustainable forest management performance correlated strongly with that country's lack of future directed temporal orientation. The gravity with which Suriname is unable to provide secure property rights does not correlate with the moderate sustainable forest management performance it exhibits. The findings of this research provide a new way to improve sustainable forest management and inform best practice for the success of the United Nations Reduced Emissions from Deforestation and Degradation (REDD) program. The findings also identify a new tool, social values towards time, to tackle global climate change mitigation challenges.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: William Moomaw.; Committee: William Martel, and Patrick Verkooijen.; Keywords: Sustainability, International relations, and Political Science.